2013
DOI: 10.1590/s1516-89132013000400014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thickness on properties of plasticized oat starch films

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…Furthermore, the thickness of the film could possibly influence film transparency. Galdeano et al reported that increased film thickness could also increase film opacity or the film becoming less transparent. Transparency is an important characteristic of food packaging, especially when the film is used for covering food products.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the thickness of the film could possibly influence film transparency. Galdeano et al reported that increased film thickness could also increase film opacity or the film becoming less transparent. Transparency is an important characteristic of food packaging, especially when the film is used for covering food products.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical Properties : The mechanical properties were determined according to the D882‐91 method and the parameters analyzed were tensile strength (TS − MPa) and elongation at break (EB − %) performed in a Texture Analyser TA.XT Plus (Texture Technologies Corp., Hamilton, Canada). The method described earlier was used.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of açaí increased the WVP (P> 0.05), which can be explained by an increase of thickness, since greater thickness directly increasea WVP 59 . It was also observed in some oat starch films produced with varied plasticizers 60 . Starch films developed with hydrophilic materials present positive relationship between thickness and WVP, due to the interaction of water with the polymer matrix leading to structural changes caused by swelling of the hydrophilic matrix.…”
Section: Water Vapor Permeability Of Filmsmentioning
confidence: 82%
“…Starch films developed with hydrophilic materials present positive relationship between thickness and WVP, due to the interaction of water with the polymer matrix leading to structural changes caused by swelling of the hydrophilic matrix. This affects the film structure causing internal stresses that affects water permeation 60 . WVP values were close to those found for cassava starch and soy protein 29 films and for cassava starch and acerola pulp films 8 .…”
Section: Water Vapor Permeability Of Filmsmentioning
confidence: 99%